PENGARUH EDUKASI MELALUI BOOKLET TERHADAP PENGETAHUAN PENDERITA HIPERTENSI TENTANG PENCEGAHAN STROKE (Politeknik Kesehatan Kemenkes Bandung, 2021)
Background: Based on data from WHO (World Health Organization), hypertension affects 22% of the world's population. West Java ranks second as the province with the highest cases of hypertension in Indonesia, which is 39.6%. The prevalence of hypertension at the Nanjungmekar Health Center increased in 2019 by 23% and became the first rank of 10 disease patterns and outpatient morbidity rates. Objective: To determine the effect of education through booklets on the knowledge of hypertension sufferers about stroke prevention in Posbindu RW 05 Sangiang Village, Rancaekek District, Bandung Regency. Methods: Quasi-experimental one group pretest posttest. The subjects of this study were 32 patients with hypertension. Univariate analysis with mean and bivariate with paired T-test. Results: The results were mean pretest 55.16 posttest 83.66 with an increase of 28.50. There was an effect of booklets on knowledge with a P value of 0.000 <0.05. Conclusion: There the effect of education through booklets on the knowledge of hypertension sufferers about stroke prevention in posbindu RW 05 Sangiang Village, Rancaekek District, Bandung Regency. Recommendation: It is hoped that this booklet media can be a source of information that can be utilized and disseminated by health workers and cadres at posbindu in preventing stroke for people with hypertension.